War, Demobilization and Memory
XVIII, 416 p.
Keywords: The years from 1770 to 1830 were scarred by war throughout the Atlantic world. These were wars about empire and global hegemony, as well as struggles of liberation and decolonization. During this era the Atlantic became a highway for exchange not only of peoples and commodities, but also of ideas and cultural practices. New forms of mass warfare, for which patriotic-national propaganda mobilized soldiers and civilians alike, characterized these conflicts in Europe and the Americas. The contributors to this volume, all established experts in their field, examine the processes of military, economic, political, social and cultural demobilization after these wars, not only by states but also by local communities and individuals, and explore the long-term legacy of these conflicts. They discuss how their aftermath influenced politics, society and culture, including the gender order, and ask what shaped the contested and changing memories of these wars in the decades that followed.